The spatial‐temporal expression and functional divergence of bach homologs in zebrafish Danio rerio. Issue 4 (16th March 2016) - Luo, Q.; Wu, C.; Sun, S.; Lu, F.; Xie, L.; Zhao, H.; Zhong, X.; Zhou, Q.
Abstract : The spatial‐temporal expressions of bach1a, bach1b, bach2a and bach2b in early development of zebrafish Danio rerio embryos were examined in the present study by whole mount in situ hybridization. Transcripts of all genes were found at the one cell stage, suggesting that these four genes are maternally inherited. From the phylogenetic analyses, Bach1a and Bach1b from fishes form a well‐supported group with two sub‐groups. Bach2a and Bach2b, however, did not fall into one clade, suggesting that Bach2 proteins diverged faster or earlier than Bach1 proteins in fishes. The differentially regulated expression of the exocrine zymogen (such as the trypsin‐like gene, tryl ) of both paralogs of bach1 and bach2, respectively, showed that their functions are still active and already divergent, coinciding with subfunction partitioning.